Usability evaluation model for mobile e-book applications - Matraf, Munya Saleh Saeed Ba (2017)
Evaluation for mobile e-book applications are limited and did not address all the important usability measurements. Hence, this study aimed to identify the characteristics that affect user satisfaction on the usability of mobile e-book applications. Five characteristics that have a significant effect on the user satisfaction of mobile e-book applications have been identified namely readability, effectiveness, accessibility, efficiency, and navigation. A usability evaluation was conducted on three mobile e-book applications namely Adobe Acrobat Reader, Ebook Reader, and Amazon Kindle. 30 students from Universiti Utara Malaysia evaluated the mobile e-book applications and their satisfaction was measured using questionnaire. The outcomes discovered that the five characteristics (i.e., readability, effectiveness, accessibility, efficiency, and navigation) have a significant positive relationship with user satisfaction. This provides insights into the main characteristics that increase user satisfaction. It also designed a task scenario and a satisfaction questionnaire which help in evaluating mobile e-book applications.